EKSPLORASI FAKTOR PENGHAMBAT DALAM MENGADOPSI GREEN MARKETING PRACTICES PADA IKM RENDANG DI KOTA PADANG - Nadya Aulia; Maruf; Hafiz Rahman (Journal Publicuho, 2024)
The purpose of this study is to explore the inhibiting factors in the implementation of green marketing practices in rendang SMEs in Padang City. This study uses a qualitative method that aims to obtain a clear picture of a problem, which will be focused on collecting data or information on the object. The results of the research findings and the results of the NVivo 12 plus Project Map analysis, various obstacles felt by SMEs actors to implement green marketing practices, namely government regulations, resources, organizational management, costs and awareness. This is due to the lack of involvement in long-term environmental concerns when producing products. In general, SMEs in rendang businesses focus more on the taste of food, product durability and good quality to reach consumers. In this case, there is no involvement in environmental aspects to minimize environmental impacts ranging from products, production sites, and price to product promotions.